Dynamic Alterations of miR-34c Expression in the Hypothalamus of Male Rats after Early Adolescent Traumatic Stress - Chuting Li; Yuan Liu; Dexiang Liu; Hong Jiang; Fang Pan (Neural Plasticity)
Several types of microRNA (miRNA) overexpression in the brain are associated with stress. One of the targets of miR-34c is the stress-related corticotrophin releasing factor receptor 1 mRNA (CRFR1 mRNA). Here we will probe into the short-term effect and long-term effect of early adolescent traumatic stress on the expression of miR-34c and CRFR1 mRNA. Traumatic stress was established by electric foot shock for six consecutive days using 28-day rats. The anxiety-like behaviors, memory damage, CRFR1 protein, CRFR1 mRNA, and miR-34c expression were detected in our study. The results of our study proved that exposure to acute traumatic stress in early adolescent can cause permanent changes in neural network, resulting in dysregulation of CRFR1 expression and CRFR1 mRNA and miR-34c expression in hypothalamus, anxiety-like behavior, and memory impairment, suggesting that the miR-34c expression in hypothalamus may be an important factor involved in susceptibility to PTSD.